2006
DOI: 10.1002/ange.200601432
|View full text |Cite
|
Sign up to set email alerts
|

Lichtgesteuerte Faltung und Entfaltung einer Collagen‐Tripelhelix

Abstract: Strukturen aufgedröselt: Die beiden Seitenketten eines Collagenpeptids mit (2S,4S)‐Mercaptoprolin an zwei definierten Positionen wurden durch ein Diiodazobenzol als Verbindungsstück verknüpft. Das Peptid faltet mit der trans‐konfigurierten Azobenzolklammer (orange) in eine Tripelhelix (grün, blau und grau) und entfaltet bei Belichtung bei 330 nm. Die lichtgesteuerten Faltungs‐ und Entfaltungsvorgänge sind völlig reversibel, sodass dieses System für ultraschnelle Spektroskopie prädestiniert ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
0
26
0
6
Order By: Relevance
“…For side-chain cross-bridging of the bis-cysteinyl peptides with the bifunctional azobenzene-4,4'-bis-N-(4-chloro-2-butynenyl)carboxyamide reagent, [9] the (S)-tert-butylthio groups were removed by reduction of the asymmetric disulfide with tributylphosphine in trifluoroethanol/water, and the azobenzene-chloro derivative was converted to the bisiodo compound by the Finkelstein reaction with sodium iodide in acetone. This conversion does not occur quantitatively and minor amounts of educt as well as of monoiodo derivatives were detectable in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For side-chain cross-bridging of the bis-cysteinyl peptides with the bifunctional azobenzene-4,4'-bis-N-(4-chloro-2-butynenyl)carboxyamide reagent, [9] the (S)-tert-butylthio groups were removed by reduction of the asymmetric disulfide with tributylphosphine in trifluoroethanol/water, and the azobenzene-chloro derivative was converted to the bisiodo compound by the Finkelstein reaction with sodium iodide in acetone. This conversion does not occur quantitatively and minor amounts of educt as well as of monoiodo derivatives were detectable in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Peptides were synthesized by using a Pioneer Peptide Synthesis System (Model GEN600611, PerSeptive Biosystems, Framingham, USA) on a 0.1-mmol scale on TentaGel S Ram resin (Rapp Polymere, Tübingen, Germany) by applying the Fmoc/tBu strategy and tert-butylthio protection of the Cys residues. Fmoc cleavage was achieved with 20 % piperidine in DMF for 5 min and couplings were performed with 4 equiv of Fmoc-Xaa-OH/ HOBt/HBTU/DIPEA (1:1:1:2) (Fmoc = 9-fluorenylmethyloxycarbonyl, HOBt = 1-hydroxybenzotriazole, HBTU = 2-(1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluoro phosphate) in DMF for 60 min, whereas Fmoc-Pro-OH required double couplings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] Such azobenzene-alkylated peptides have previously been used for the photocontrol of protein-protein and protein-DNA interactions. [17][18][19][20][21][22] Here we demonstrate the versatility of photocontrolled nanoswitches in targeting interfaces between proteins and RNA.…”
mentioning
confidence: 93%
“…A number of reports have demonstrated that sophisticated and stimuli-responsive materials and surfaces can be assembled by a careful combination of orthogonal noncovalent interactions. [1][2][3][4][5][6][7][8] The photoisomerization of azobenzene has been the molecular basis for a range of photosensitive supramolecular materials, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] including photoresponsive vesicles. [26][27][28][29][30] Azobenzenes constitute a well-known class of photoresponsive compounds that can be reversibly isomerized from trans to cis by irradiation at 350 nm and from cis to trans by irradiation at 455 nm.…”
Section: Introductionmentioning
confidence: 99%